SISTEM AKUNTANSI PEMBELIAN PERSEDIAAN (KAYU ACASIA MANGIUM) PADA CV. ALPAN TONDON PERKASA - Alvan Pranata Saputra; Suyanto Suyanto; Ardiansyah Japlani (Universitas Muhammadiyah Metro, 2020)
Alvan, pranata, saputra. Inventory accounting system (acasia mangium wood) on CV. Alpan Tondon Perkasa.The final task. The d3 accounting study program, the faculty of economics and business of metro university. Data collection in this final assignment USES documentation methods and interviews. Data obtained with apainkiller method is then analyzed using qualitative descriptive analysis. A qualitative antective method is amethod not based on quantitative (sum) calculations but rather on the form of statements and descriptions thatwill then be systematically arranged in the final form of duty. From the data analysis and then to compare thetheory and fact that is a descriptive procedure of the press system.